How One Health approach contributes to sustainable food systems transformation for sustainable healthy diets - Sinh Dang-Xuan; Unger, Fred; Hung Nguyen-Viet (International Livestock Research Institute, 2023)
This presentation gives an overview of One Health and sustainable healthy diets, within the context of food safety innovations and interventions in Cambodia and Vietnam.